Mendelian Randomization Analysis reveals Inverse Genetic Risks between Skin Cancers and Vitiligo - Sarem Rashid; Ivan Molotkov; Nikolai Klebanov; Michael Shaughnessy; Mark J. Daly; Mykyta Artomov; Hensin Tsao (JID Innovations, 2023)
Several observational studies have demonstrated a consistent pattern of decreased melanoma risk among patients with vitiligo. More recently, this finding has been supported by a suggested genetic relationship between the two entities, with certain variants significantly associated with an increased risk of melanoma, basal cell carcinoma, and squamous cell carcinoma but a decreased risk of vitiligo. We compared 48 associated variants from a recently published GWAS and identified three variants—located in the TYR, MC1R-DEF8, and RALY-EIF2S2-ASIP-AHCY-ITCH loci— that correlated with an increased risk for melanoma, basal cell carcinoma, and squamous cell carcinoma and a decreased risk for vitiligo. We then used results of skin cancers and vitiligo GWAS to compare the shared genetic properties between these two traits through an unbiased Mendelian randomization analysis. Our results suggest that the inverse genetic relationship between common skin cancers and vitiligo is broader than previously reported owing to the influence of shared genome-wide significant associations.